Polymeric Nanomicelles Loaded with Anandamide and Their Renal Effects as a Therapeutic Alternative for Hypertension Treatment by Passive Targeting - Virna Margarita Martín Giménez; Marcela Analía Moretton; Diego Andrés Chiappetta; María Jimena Salgueiro; Miguel Walter Fornés; Walter Manucha (MDPI AG, 2023)
We have previously demonstrated significant in vitro natriuretic effects of anandamide (AEA) nanoformulation in polymeric nanoparticles, whose size prevents their accumulation in organs, such as the kidneys. Therefore, it is of particular interest to design and test nanostructures that can pharmacologically accumulate in these organs. In this regard, we prepared and characterized polymeric nanomicelles (~14 and 40 nm). Likewise, their biodistribution was determined. Spontaneously hypertensive rats (SHR) and normotensive rats (WKY), n = 3 per group, were divided into five treatment conditions: control, sham, free AEA freshly dispersed in aqueous solution or 24 h after its dispersion, and AEA encapsulated in nanomicelles. The kidneys were the main site of accumulation of the nanoformulation after 24 h. Freshly dispersed free AEA showed its classical triphasic response in SHR, which was absent from all other treatments. Nanoformulated AEA produced a sustained antihypertensive effect over 2 h, accompanied by a significant increase in fractional sodium excretion (FSE %). These effects were not observed in WKY, sham, or free AEA-treated rats after 24 h of its aqueous dispersion. Without precedent, we demonstrate in vivo natriuretic, diuretic, and hypotensive effects of AEA nanoformulation in polymeric nanomicelles, suggesting its possible use as a new antihypertensive agent with intravenous administration and passive renal accumulation.